Pendekatan Elaboratif Pembelajaran Pendidikan Agama Islam (PAI) Berbasis Budaya Lokal sebagai Upaya Membentuk Sikap Toleransi Peserta Didik - Sahdan; Kibtiyah, Asriana (Kartika: Jurnal Studi Keislaman, 2025)
Islamic Religious Education (PAI) is not merely intended to enhance students’ religious knowledge but also to cultivate character rooted in values of coexistence and tolerance. This study aims to analyze the application of an elaborative approach in PAI learning integrated with local culture and its role in shaping students’ tolerance attitudes at SMP Islam al-Manan Bagik Nyaka Aikmel, East Lombok. The research focuses on: (1) the implementation of PAI learning and local culture, (2) the application of the elaborative approach in fostering students’ tolerance, and (3) supporting and inhibiting factors of the elaborative approach in the learning process. This research employed a qualitative case study method. Data were collected through interviews and documentation, and analyzed using domain analysis techniques through stages of data reduction, data presentation, and conclusion drawing. The findings reveal that the elaborative approach in PAI learning, when integrated with local cultural practices such as the selakaran tradition involving the recitation of Kitab al-Barzanji during rowahan for hajj pilgrims, is effective in shaping students’ tolerance. This integration is further reinforced by the values of tolerance nurtured at Pesantren al-Manan, particularly in responding to the presence of salafi-wahhabi thought in the surrounding community. The study highlights the importance of synergizing religious education and local culture as a strategic effort to foster tolerance among young generations.